Impulsivity and social support as intervening and interactive variables in the link between childhood socioeconomic status and mental health among first-year college students - Kong, Yiting; Su, Zhewei; Wang, Rui; Tan, Jianyu; Ran, Pan; Xu, Xiaoming; Wang, Wo; Hong, Su; Zhang, Qi; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundSignificant attention has been given to the mental health of college students, especially first-year college students, with childhood socioeconomic status (SES) identified as a key factor. This study investigated the correlation of impulsivity and social support in the relationship between childhood SES and current mental health, with a focus on depressive and anxiety symptoms, in first-year college students.MethodsA cross-sectional study was designed, surveying 6,378 first-year students (mean age = 20.98) at a university in Chongqing, China. The survey participants were 63.4% female and 36.6% male. The participants completed an online questionnaire which included Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Brief Barratt Impulsiveness Scale, Multidimensional Scale of Perceived Social Support, and a 7-point scale to measure childhood SES. Descriptive statistics and correlation analyses were conducted for these variables, and the data examined further using a moderated conditional effect model with PROCESS macro (Model 8).ResultsThe analysis revealed that lower childhood SES showed small to moderate negative correlations with impulsivity (r = -0.224, p < 0.01, small effect) and heightened symptoms of depression (β = -0.235, p < 0.01) and anxiety (β = -0.197, p < 0.01). Impulsivity shared variance with the link between childhood SES and both depressive (β = 0.386, SE = 0.011, p < 0.001) and anxiety symptoms (β = 0.315, SE = 0.012, p < 0.001). Higher levels of social support were linked to attenuated associations between low childhood SES and both impulsivity (β = -0.064, SE = 0.011, p < 0.01) and depressive symptoms (β = -0.029, SE = 0.010, p < 0.01). However, social support was not significantly associated with the link between childhood SES and anxiety symptoms.ConclusionOur findings demonstrate that impulsivity serves as a partial intervening variable in the relationship between childhood SES and the mental health of first-year college students. However, higher levels of social support were linked to weaker negative associations between impulsivity and both childhood SES and mental health. Interventions that focus on managing impulsivity and increasing social support for first-year college students from low socioeconomic backgrounds could be effective strategies for improving their mental health.